A STUDY ON EMPLOYEE SAFETY AND WORKPLACE HAZARDS IN RELATION TO PERFORMANCE OF JEWELLERY MANUFACTURING INDUSTRIES - Jayalakshmi, V; Panchanatham, N (Journal of Contemporary Research in Management (JCRM), 2017)
Organisations are obliged to provide with a safe and healthful environment. Health is a general state of physical, mental and emotional well-being. Safety is protection of a person’s physical health. The main purpose of health and safety polices is the safe interaction of people and the work environment. Poor working conditions affect employee performance badly. Employees may find it difficult to concentrate on work. It would be too taxing for them to work for longer hours. Their health may suffer. Accidents and injuries may multiply causing enormous financial loss to the company. Absence and turnover ratio may grow. A company with a poor safety record may find it difficult to hire and retain skilled labour force. The overall quality of work may suffer. Many deaths, injuries and illness occur because of safety violations, poor equipment design or gross negligence. Thus, the research study focuses on protecting employees from workplace hazards particularly among Jewellery manufacturing industries for increasing work performance. A questionnaire is designed to assess employee safety, workplace hazard and performance of employees in Jewellery manufacturing industries. First, the employee safety and workplace hazard assessment form considers the consequences of exposure to or contact with the hazard. Could it result in a minor injury or a permanent disability? Could it cause minor equipment damage or extensive damage to the premises? There are two types of hazards in workplace, they are: health and safety hazards. Health hazards can lead to illnesses or disorders such as inflamed or irritated joints (e.g., tendonitis, epicondylitis), skin diseases (such as dermatitis), carpal tunnel syndrome, hernias and various cancers. Some health hazards can also have harmful reproductive effects. Safety hazards can lead to traumatic types of injuries such as sprains, bruises, fractures and cuts. In this study among Jewellery indusries we have considered six departments namely; wax, filing, buffing, stone setting, steam bath and colouring, which affects employees health based on the severity, frequency, probability and significance of workplace hazards. Second, the performance assessment included 9 questions on the measures taken against hazards by company, supervisor and managers in improving the performance of individual and organization. Based on the review, it is revealed that effective health and safety practices led to high profitability and high productivity. For this, the HR department should have to monitor health and safety of employees daily, coach them to be safety conscious, investigate accidents, observe health and safety behavior of employees, monitor workplace for security problems, communicate with employees to identify potentially difficult employees, and follow safety provisions and security procedures and recommend changes as needed. So, for increasing performance and organisational growth, HR managers should focus on primary health and safety responsibilities towards employee’s health.